Mechanical analysis of PDMS material using biaxial test - Ribeiro, J.E. (2019)
Polydimethylsiloxane (PDMS) materials are classified as a silicone and commonly present a hyperelastic behaviour. Many researchers have studied PDMS in recent years, motivated by its applications in the biomedical field. In the present manuscript, a biaxial tensile test performed at different speeds is described. The displacement field for the different experimental test conditions is measured using the digital image correlation technique. Numerical studies were also carried out using the most popular constitutive models, namely Mooney-Rivlin, Yeoh and Ogden, for comparison with the experimental measurements. From the experimental displacement profile taken along the central section of each sample, that this tensile test presents linear behaviour; it is an independent speed test. The same conclusion can be found from the numerical results. The results of the numerical simulation show that they are strongly dependent on the constitutive model of the material. The numerical simulations with the Yeoh model presented the most accurate results for PDMS behaviour. Another important conclusion is that the digital image correlation technique is well suited for the analysis of hyperelastic materials.